Неологізми фандомного походження в українській мові як об’єкт мовознавства - Андрея Певсе; Асталош Каталіна; Pősze Andrea; Asztalos Katalina; Andreya Pevse (Casa Cărţii de Ştiinţă-Editura RCR Editorial, 2025)
Abstract. Fandom-Derived Neologisms in the Ukrainian Language as an Object of Linguistics. The article explores the linguistic characteristics of fan communities (fandoms) as a distinct cultural and communicative phenomenon actively developing in the context of modern information society. The focus is placed on the analysis of fan-based neologisms – new lexical units that emerge within fandom activity to denote novel realities, concepts, social roles, and forms of interaction. These neologisms are examined as markers of group identity, means of symbolic self-expression, and tools for integration within the community, as well as linguistic elements that influence the development of contemporary Ukrainian vocabulary. The study analyzes the structure, functions, and discursive features of fan-related neologisms, as well as their dissemination in social media, online communication, and mass media. It is demonstrated that such lexical items reflect not only the dynamic evolution of vocabulary but also broader cultural and communicative shifts tied to mass culture, digital interaction, and social behavior. The paper outlines prospects for further research into fandom-related lexis within the frameworks of modern linguistics, sociolinguistics, and media linguistics.

Резюме. У статті розглянуто мовні особливості фанатських спільнот (фандомів) як специфічного культурного й комунікативного явища, що активно роз-вивається в умовах сучасного інформаційного суспільства. Основну увагу зосередже-но на аналізі фанатських неологізмів – нових лексичних одиниць, що виникають у межах фандомної діяльності для позначення нових реалій, понять, ролей та форм взаємодії. Неологізми розглядаються як маркери групової ідентичності, засоби символічного самовираження та інтеграції до спільноти, а також як елементи, що справляють помітний вплив на розвиток лексичної системи сучасної української мови. У дослідженні проаналізовано структуру, функції та дискурсивні особливості фанатських неологізмів, їхнє поширення в соціальних мережах, інтернет-комунікації та мас-медіа. Доведено, що ці мовні одиниці відображають не лише еволюцію лекси-кону, а й глибші процеси, пов’язані зі змінами в масовій культурі, цифровій комунікації та соціальній взаємодії. Окреслено перспективи подальшого вивчення фандомної лексики в межах сучасної лінгвістики, соціолінгвістики та медіалінгвістики.
Fandom-Derived Neologisms in the Ukrainian Language as an Object of Linguistics
Keywords: неологізми; мовознавство; ідентичність; neologisms; linguistics; identity